2016
DOI: 10.1159/000448079
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging-Based Thalamic Segmentation in Deep Brain Stimulation for Chronic Pain Conditions

Abstract: Background/Aims: Thalamic deep brain stimulation (DBS) for the treatment of medically refractory pain has largely been abandoned on account of its inconsistent and oftentimes poor efficacy. Our aim here was to use diffusion tensor imaging (DTI)-based segmentation to assess the internal thalamic nuclei of patients who have undergone thalamic DBS for intractable pain and retrospectively correlate lead position with clinical outcome. Methods: DTI-based segmentation was performed on 5 patients who underwent sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…In previous studies, probabilistic and deterministic approaches were used for thalamic targeting in ET patients ( Pouratian et al, 2011 , Kim et al, 2016 , Hyam et al, 2012 , Kincses et al, 2012 , Sedrak et al, 2011 ). Pouratian et al (2011) reported a new method of targeting patient-specific therapeutic thalamic target for the treatment of tremor based on individualized probabilistic tractography analysis of thalamic connectivity patterns to premotor and supplementary motor cortices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, probabilistic and deterministic approaches were used for thalamic targeting in ET patients ( Pouratian et al, 2011 , Kim et al, 2016 , Hyam et al, 2012 , Kincses et al, 2012 , Sedrak et al, 2011 ). Pouratian et al (2011) reported a new method of targeting patient-specific therapeutic thalamic target for the treatment of tremor based on individualized probabilistic tractography analysis of thalamic connectivity patterns to premotor and supplementary motor cortices.…”
Section: Discussionmentioning
confidence: 99%
“… Pouratian et al (2011) reported a new method of targeting patient-specific therapeutic thalamic target for the treatment of tremor based on individualized probabilistic tractography analysis of thalamic connectivity patterns to premotor and supplementary motor cortices. The same approach ( Kim et al, 2016 ) was validated for the definition of Vim in a tremor-dominant Parkinson's disease patient. Others have used probabilistic tractography to explore the individual thalamic nuclei connectivity profiles and to reveal the inter-individual variability of the anatomical position of nuclei areas ( Hyam et al, 2012 , Kincses et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Periventricular gray/PAG was targeted in eight patients (six responders), among whom four also received simultaneous stimulation in the ventroposterolateral and ventroposteromedial nuclei (VPL/VPM) ( 47 , 49 , 50 ). Those with suboptimal outcomes (one non-responder and one responder who subsequently failed) had electrodes which were found to be too medial to the VPL/VPM region ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…This review focuses specifically on the motor thalamus and DRTT; however, some of the techniques described can be applied to parcellate other functional and anatomic regions of the thalamus, including the anterior nuclear group in the treatment of epilepsy and limbic system disorders [34], specific sensory [35-38], and relay nuclei [39-41] and nuclei implicated in multiple sclerosis [42, 43], depression [44], Alzheimer’s disease [45], and Parkinson’s disease (PD) [46]. If these methods prove reliable, they may provide valuable opportunities to study pathophysiology in vivo by evaluating volumetric (and, possibly, functional) changes in specific nuclei in a variety of neurodegenerative and psychiatric disorders [47].…”
Section: Introductionmentioning
confidence: 99%